The analysis of BTS’s speech on sustainable development goals moment at the 76th united nation general assembly - Rifdah Yuliana; Syamsi Edi (Universitas Panca Sakti Bekasi, 2022)
The United Nations General Assembly (UNGA) is a unique forum for multilateral debate on the full range of international concerns covered by the UN Charter. Each of the United Nations' 193 member states has the same voting rights. The United Nations' Sustainable Development Goals (SDGs) are 17 goals consist of 169 measurable outcomes and timeframes (UN). This agenda was created in response to world leaders' demands for concrete actions to address the benefits of humans and the planet, such as poverty, inequality, and climate change. The film of BTS explores the story of a generation that affected by the pandemic. While many people feel hopeless as a result of squandered opportunities, the story of BTS gives them hope. Throughout the ongoing COVID-19 pandemic, they encourage young people to look forward to brighter days.